2018
DOI: 10.1136/bjophthalmol-2018-312516
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of vessel density measurements using optical coherence tomography angiography in retinal diseases

Abstract: AimTo analyse the repeatability of vessel density (VD) measurements using optical coherence tomography angiography (OCTA) in patients with retinal diseases.MethodsTwo consecutive VD measurements using OCTA were analysed prospectively in patients with retinal diseases (diabetic macular oedema (DME), retinal vein occlusion (RVO) with macular oedema, epiretinal membrane (ERM), wet age-related macular degeneration (AMD)). The intraclass correlation coefficient (ICC), coefficient of variation (CV) and test-retest S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 23 publications
(20 reference statements)
3
51
0
1
Order By: Relevance
“…These OCTA parameters also showed reasonable repeatability in patients with various ophthalmic diseases in other studies (Lee et al. ; Venugopal et al. ,).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…These OCTA parameters also showed reasonable repeatability in patients with various ophthalmic diseases in other studies (Lee et al. ; Venugopal et al. ,).…”
Section: Introductionsupporting
confidence: 66%
“…This issue was discussed in our previous study (Lee et al. ). The ICCs for central VDs and PDs were 0.887 and 0.847; thus, the repeatability of central measurements seemed high, whereas the ICCs for the inner and full area of VDs and PDs were lower than those for the central area.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Additionally, studies for repeatability in pathologic eyes have recently been reported. Lee et al [19] reported high repeatability of vessel density, measured automatically, in retinal diseases of diabetic macular edema, retinal vein occlusion, epiretinal membrane, and wet age-related macular degeneration. In all four retinal diseases, the ICC and CV of the full vessel densities were 0.812 and 6.72%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast with other fundus imaging techniques such as fundus uorescein angiography (FFA), OCTA has the advantage of quantitatively visualizing the vessel network and retinal nerve ber layer-by-layer. Repeatability is found to be satisfactory for measuring the parameters of macula and ONH [6], and repeated measurements using the same device are credible [7,8]. A variety of OCTA parameters concerning the macula or ONH have been explored, including VD of the super cial capillary plexus (SCP) and the deep capillary plexus (DCP) layer, foveal avascular zone (FAZ) parameters and RNFL thickness parameters.…”
Section: Introductionmentioning
confidence: 99%